Diaminotetrazine based mesoporous C3N6 with a well-ordered 3D cubic structure and its excellent photocatalytic performance for hydrogen evolution. Issue 34 (17th August 2017) - Talapaneni, Siddulu Naidu; Mane, Gurudas P.; Park, Dae-Hwan; Lakhi, Kripal S.; Ramadass, Kavitha; Joseph, Stalin; Skinner, William M.; Ravon, Ugo; Al-Bahily, Khalid; Vinu, Ajayan
Abstract : Synthesis and excellent photocatalytic H2 evolution performance of diaminotetrazine based highly ordered 3D mesoporous carbon nitrides (MCN-9) with C3 N6 stoichiometry prepared by employing KIT-6 silica template has been demonstrated. Abstract : Novel nitrogen enriched diamino- s -tetrazine based highly ordered 3D mesoporous carbon nitride (MCN-9) hybrid materials with a body centered cubic Ia 3 d structure having high specific surface areas, large pore volumes, and tunable pore diameters were prepared by employing 3D body centered cubic KIT-6 mesoporous silica having a gyroidal porous structure and various pore diameters as the sacrificial hard template through a simple self-condensation followed by polymerization reaction of aminoguanidine hydrochloride inside the nanochannels of the KIT-6 template. Characterization results reveal that the prepared materials exhibit a 3D porous structure with well-defined mesopores and possess excellent physical parameters including high surface areas (157–346 m 2 g −1 ), large pore volumes (0.36–0.63 cm 3 g −1 ), different pore diameters (5.5–6.0 nm) and a high N/C ratio of 1.87, which is much higher than that of ideal C3 N4 (1.33). The deep yellow colored MCN-9 with a 3D porous structure also shows good absorption properties with a tunable narrow bandgap of 2.25–2.5 eV, which is again much lower than that of C3 N4 (2.7 eV) and helps to achieve much higher photocatalytic water splitting activity than non-porous C3 N4 and other carbon nitrides under visible light irradiation.